Fast charging stations placement and electric network connection methodology for electric taxis in urban zones - Mello, Igoor Morro [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
In recent years, the use of electric vehicles in urban zones has been intensified. As a policy of increasing the penetration of electric vehicles and reducing air pollution, electric taxis have been introduced into transportation systems. They need special attention because of its different driving patterns. In contrast to private electric vehicles, which can be recharged for a long period, electric taxis need to recharge only for a short time due to their constant operation. Therefore, fast charging stations are required to meet the demand for recharging electric taxis and should be located at strategic places. In addition, an analysis must be performed to connect these stations in the electric network. To improve their allocation and connectivity, this work presents a methodology to help in decision making for installing fast charging stations, considering as criteria: locations with greater flow of electric taxis and low level of state of charge, the available physical space to carry out their recharge and cost functions for the connection of charging stations. The result of the proposal is a map with the location of fast charging stations and analysis of the lowest cost places for connection to the network. The methodology is tested in a medium-sized city in Brazil, showing the importance of this map and cost functions in decision making. The proposal is compared with another methodology, showing that the proposed method considers different criteria and creates a better spatial distribution of charging stations giving better options to the owners of electric taxis.

Nos últimos anos, o uso dos veículos elétricos nas zonas urbanas tem se intensificado. Como política para o aumento na penetração de veículos elétricos e reduzir a poluição do ar, os táxis elétricos vem sendo introduzidos nos sistemas de transporte. Eles necessitam de atenção especial devido aos seus diferentes padrões de condução. Em contraste com os veículos elétricos privados, que podem ser recarregados por um longo período, táxis elétricos necessitam de recarga em um curto período de tempo devido a sua constante operação. Portanto, estações de recarga rápida são necessárias para receber a demanda de recarga dos táxis elétricos e devem estar localizadas em locais estratégicos. Além disso, uma análise deve ser realizada para a conexão destas estações com a rede elétrica. Para melhorar sua alocação e conectividade, este trabalho apresenta uma metodologia para auxiliar na tomada de decisão da instalação de estações de recarga rápida considerando como critérios: locais com maior fluxo de táxis elétricos e baixo nível de carga nas baterias, espaço físico disponível para realizar o carregamento e funções de custo para a conexão das estações de recarga. Os resultados da proposta são mapas com a localização das estações de recarga rápida e análise dos locais de menor custo para a conexão com a rede elétrica. A metodologia é testada em uma cidade de médio porte no Brasil, mostrando a importância dos mapas e funções de custo na tomada de decisão. A proposta é comparada com outras metodologias, mostrando que esta metodologia proposta considera diferentes critérios e cria uma melhor distribuição espacial para as estações de recarga, dando melhores opções aos donos dos táxis elétricos.
Metodologia de alocação espacial e conexão com a rede elétrica de estações de recarga rápida para táxis elétricos em zonas urbanas
Keywords: Charging stations; Electric taxis; Power distribution system planning; Spatial load forecasting; Transportation networks; Urban infrastructures; Estações de recarga; Infraestrutura urbana; Planejamento de sistemas de distribuição de energia; Previsão espacial de carga; Rede de transportes; Táxis elétricos